PERENCANAAN PRODUKTIVITAS KERJA DARI HASIL EVALUASI PRODUKTIVITAS DENGAN METODE FISHBONE DI PERUSAHAAN PERCETAKAN KEMASAN PT.X - Murnawan, Heri (Heuristic, 2016)
Productivity is an important factor that affects the progress and setbacks of a company. Evaluation and planning is indispensable productivity after making measurements and it will be the foundation to move on to the next cycle of the productivity improvements in the future. A method that can be used in the evaluation is a method Fishbone Diagram and continue planning with Objective Matrix in accordance with the results of previous measurements. In the evaluation and planning, the selection of primary and secondary causes is an important step, because the selection can be used to determine the cause of the decline in productivity in the measurement period, the planning for the next period , and improved productivity for the company. The study took place in Packaging Printing Company PT " X " , Rungkut Industry , Surabaya in January - June 2013. The purpose of this follow-up study is to evaluate and analyze productivity by using a Fishbone Diagram productivity and plan for the next period in accordance with the method of measuring the PT " X " . The research was conducted on the following five criteria: the target production, raw materials, energy, labor and machine hours . Evaluation and planning is done to determine the decrease in productivity as well as during the planning period January 2013 - July 2013. The results showed the indicators of productivity that have the most dominant influence on the achievement levels of labor productivity in the enterprise is the criteria of productivity Good Product Quantity / Quantity Production Target , Good Product Quantity / Use of Raw Materials , Good Product Quantity / Quantity Energy Use . Because the productivity of each of these criteria have a large enough weight that is above 19 %. Changes in the level of achievement of performance criteria in all three partial indicators of productivity are always followed by significant changes in the achievement of performance indicators in total. Kata kunci: Perencanaan Produktivitas Kerja, Diagram Fishbone, Industri Kemasan